Potential drugs for asthma allergy: in silico study and ADMET prediction of secondary metabolites derived from Curcuma longa Linn. rhizome - Pratama, Yusuf Alif; Marhaeny, Honey Dzikry; Rahmadi, Mahardian; Ozdemir, Kevser; Bardakci, Hilal; Hasan, Ahmed Abdallah; Kleuser, Burkhard; Bakhtiar, M. Taher; Khotib, Junaidi (Shahrekord University of Medical Sciences, 2025)
Introduction: An allergy is a hypersensitivity reaction generally mediated by the immune system, which is usually followed by an increase in IgE levels. The early phase of the molecular pathogenesis of allergies begins with the binding activation of the allergen and protease-activated receptor, followed by the phosphorylation of the three protein kinases. The role of p38 MAPK, ERK1/2, and JNK are integral to the pathophysiology of allergic asthma. Curcuma longa has been known as an anti-inflammatory herbal medicine that has a potential to be an asthma allergy drug. The in silico and absorption, distribution, metabolism, excretion, and toxicology (ADMET) prediction studies were conducted to identify the C. longa secondary metabolites as a potential asthma allergy drug. Those compounds suggest the molecular activity inhibition in the inflammatory pathways underlying allergic manifestations. Methods: Candidate compounds that fulfilled Lipinski’s theoretical requirements were docked to three protein kinases using Molegro Virtual Docker Version 5.5. The rerank score of each compound was compared with those of the standard ligand and existing drug. Results: At least two compounds with rerank scores consistently lower or comparable to the existing ligands and drugs, namely compound A (1,5-dihydroxy-7-(4-hydroxy-3-methoxyphenyl)-1-(4-hydroxyphenyl)-4,6-heptadien-3-one) and compound B (Bisdesmethoxycurcumin), were identified. The ADMET profile gave an outstanding result to be developed as a drug candidate. Conclusion: The secondary metabolites derived from C. longa exhibit potent inhibitory effects on those three kinases. This strategy seems to hold a significant potential for developing novel therapeutics targeting inhalant-induced allergies